At what cost is performance-based financing implemented?: novel evidence from Malawi - De Allegri, Manuela; Makwero, Chris; Torbica, Aleksandra (Health policy and planning, 2019)
Abstract. Our study estimated the full economic cost of implementing performance-based financing [PBF, the Support for Service Delivery Integration Performance